Airway Epithelial Cells Drive Airway Smooth Muscle Cell Phenotype Switching to the Proliferative and Pro-inflammatory Phenotype - O’Sullivan, M. J.; Jang, J. H.; Panariti, A.; Bedrat, A.; Ijpma, G.; Lemos, B.; Park, J. A.; Lauzon, A. M.; Martin, J. G. (Frontiers in Physiology, 2021)
The increased mass of airway smooth muscle (ASM) in the airways of asthmatic patients may contribute to the pathology of this disease by increasing the capacity for airway narrowing. Evidence for the airway epithelium as a participant in ASM remodeling is accruing. To investigate mechanisms by which airway epithelial cells induce ASM cell (ASMC) proliferation, we have employed a co-culture model to explore markers of ASMC proliferative phenotype. Co-culture with epithelial cells led to incorporation of bromodeoxyuridine (BrdU) into ASMCs, indicating augmented proliferation. Furthermore, co-cultured ASMCs possessed increased mRNA of the pro-proliferative co-transcription factor Elk1. Although the mitogen heparin-binding epidermal growth factor (HB-EGF) was augmented in co-culture supernatant, the ASMC epidermal growth factor receptor (EGFR), an effector of HB-EGF induced proliferation, did not mediate epithelial-induced proliferation. Co-culture increased the expression of mRNA for the pro-inflammatory cytokines IL-6 and IL-8 as well as the pro-proliferative micro RNA miR-210. The transcriptional repressor Max-binding protein (Mnt), a putative target of miR-210, was transcriptionally repressed in co-cultured ASMCs. Together, these data indicate that the airway epithelium-induced proliferative phenotype within ASMCs is not driven by EGFR signaling, but rather may be dependent on miR210 targeting of tumor suppressor MNT.